Beta-carotene content of carrot residue (sapal) at different stages of the processing of carrot residue powder - Nera, Zarita T.
ABSTRACT The beta-carotene content of dehydrated carrot residue (sapal), a by-product from carrot juice extraction was determined at the different stages of the dehydration process. Analytical determinations showed that it has an initial B-carotene content of 5024.59 mcg/100 g. (34796.33 mcg./100 g. dry solids, MFB) which is 50% of the amount present in carrot (FCT, 1980) and a moisture content of 85.56% prior to dehydration. A procedure for carrot residue powder (CRP) production was then developed. Adequate blanching of carrot residue was observed after 4 minutes. Cabinet drying of the residue at 60-65C for 2 1/2 - 3 hours produced a powdered product of good quality. Both the dried and powdered products had moisture contents below 13%. B-carotene analysis of the blanched, 5270.52 mcg/100 g. (47913.82 mcg/100 g. dry solids, MFB); dried, 11650.60 mcg./100 g. (13314.97 mcg./100 g dry solids, MFB); and powdered, 10539.66 mcg./100 g (11506.18 mcg./100 g dry solids, MFB). CRP was evaluated as deep orange in color, has a discernible carrot odor, a smooth but lumpy texture and was rated as like moderately. Finally, CRP was incorporated in polvoron at 15%, 25% and 40% levels by weight of flour. The polvoron with 15% level of CRP was found to be the most acceptable. Based on computations, the polvoron had a B-carotene content increase of 484 mcg./100 grams.